Positive Correlation of Family Support and Level of Anxiety in Facing Labor - Devi Septiani; Wan Anita; Rummy Islami Zalni (STIKes Patria Husada Blitar, 2023)
Anxiety that occurs in pregnant women can be reduced in various ways, one of which is with family support. Family support can provide peace, calm, and comfort for pregnant women in undergoing pregnancy in the first, second and third trimesters. The purpose of this study was to determine the correlation between family support and the anxiety level of third trimester pregnant women. This study used a quantitative method with a cross-sectional study design. The population in this study were third trimester pregnant women with purposive sampling technique. The sample in this research is 30 respondents. Data was collected using a questionnaire. The results showed that 22 respondents (73.3%) who received family support did not experience anxiety, 8 respondents did not receive family support, namely 7 respondents (23.3%) experienced mild anxiety and 1 respondent (3.3%) experienced severe anxiety . The results of the Chi Square test showed a p value (0.000 <0.05), it could be concluded that there was a correlation between family support and the level of anxiety in in facing labor in third trimester pregnant women at the Ernita Midwife Independent Practice